Implementasi Model PBL, NHT dan CCB serta Media Kantong Penyelidikan - Zain Ahmad Fauzi; Metroyadi Metroyadi; Ridha Nadhira; Siti Muslehah; Hery Orhandy (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This research was conducted using the observation method to discuss the implementation of the combination of PBL, NHT and CCB models as well as the Investigation Pockets media to improve learning activities, critical thinking skills and learning outcomes of elementary school students. This study uses a qualitative research approach with the type of preliminary study research. The subjects of this study were educators and students of class V UPTD SD Negeri 1 Liang Anggang with a total of 16 students. Data collection techniques used were observation and interviews with educators and students of class V UPTD SD Negeri 1 Liang Anggang. The data analysis of this research used qualitative descriptive. These findings indicate that in the learning process, students' learning activities are still low, critical thinking skills are not honed, and there is no interesting media. In addition, the absence of games causes the class to become monotonous and boring for students which results in less than optimal student learning outcomes.